La France et la question chypriote. De la guerre d’indépendance à la crise de 1964 - Catsiapis, Jean (Études helléniques / Hellenic Studies, 2015)
The importance of the issue and recent release of the verbatim records prompted us to include an English summary after the French article rather than an abstract.